Basal Forebrain Lactate Release and Promotion of Cortical Arousal during Prolonged Waking Is Attenuated in Aging - Wigren, Henna-Kaisa (J Neurosci, 2009)
The wake-promoting basal forebrain (BF) is critically involved in sustaining cortical arousal. In the present study, we investigated how aging affects the capacity of the BF to cope with continuous activation during prolonged waking. Increased neuronal activity induces lactate release in the activated brain area, and BF stimulation increases cortical arousal. We used in vivo microdialysis to measure lactate levels in the BF, and electroencephalography (EEG) to measure cortical arousal, during 3 h sleep deprivation (SD) in three age groups of rats. Lactate increased during SD in young but not in aged (middle-aged and old) rats. The increase in high-frequency (HF) EEG theta power (7–9 Hz), a marker of cortical arousal and active waking, was attenuated in the aged. Furthermore, a positive correlation between BF lactate release and HF EEG theta increase was found in young but not in aged rats. We hypothesized that these age-related attenuations result from reduced capacity of the BF to respond to increased neuronal activation. This was tested by stimulating the BF with glutamate receptor agonist NMDA. Whereas BF stimulation increased waking in young and old rats, lactate increase and the HF EEG theta increase were attenuated in the old. Also, the homeostatic increase in sleep intensity after SD was attenuated in aged rats. Our results suggest that an age-related attenuation in BF function reduces cortical arousal during prolonged waking. As the quality of waking is important in regulating the subsequent sleep, reduced cortical arousal during SD may contribute to the age-related reduction in sleep intensity.